Smartphone sebagai Media Edukasi pada Pasien Diabetes Mellitus: A Systematic Review - Ainul Mufidah; Ninuk Dian Kurniawati; Ika Yuni Widyawati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Background: Type 2 diabetes (T2D) is associated with various health complications and health service visits, resulting in high costs for patients and the community. As a result, worldwide exponential growth of T2D has become a major issue. One strategy is to provide electronic (e-) health interventions. This intervention can reach many individuals in cost-effective and effective way to change behavior.Objective: To find out the development of smartphones as an educational medium in patients with type 2 diabetes mellitus. Method: This Systematic Review was based on Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). The database used in this study was Scopus, Proquest and Pubmed were limited to the last 5 years of publication from 2016 to 2020, full text article and in English. The keywords used were "diabetes mellitus type 2" AND "education" AND "smartphone". This systematic review used 10 articles that fit the inclusion criteria. Results: Increased used of technology in the treatment of diabetes facilitates increased communication between nurses and patients. Social networking technology was developing at an impressive pace. Recent advances in mobile health (mHealth) have created new opportunities to improve DMT2 self-management through tools to facilitate healthy eating, exercise, and access to health services. One such innovative model involves an integrated system that connects patients via smartphone phones with their support network. Keywords: diabetes mellitus type 2; smartphone; education ABSTRAK Latar belakang: Diabetes tipe 2 (T2D) dikaitkan dengan berbagai komplikasi kesehatan dan kunjungan pelayanan kesehatan, sehingga biaya tinggi untuk pasien dan masyarakat. Akibatnya, seluruh dunia pertumbuhan eksponensial dari T2D telah menjadi isu utama. Salah satu strategi adalah untuk memberikan elektronik (e-) intervensi kesehatan. Intervensi ini dapat mencapai banyak individu dalam cara yang hemat biaya dan efektif dalam mengubah perilaku. Tujuan: Untuk mengetahui pengembangan smartphone sebagai media edukasi pada pasien diabetes mellitus tipe 2. Metode: Systematic Review ini disusun berdasarkan Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). Database yang digunakan dalam penelitian ini adalah Scopus, Proquest dan Pubmed terbatas untuk publikasi 5 tahun terakhir dari 2016 hingga 2020, full text article dan berbahasa Inggris. Kata kunci yang digunakan adalah “diabetes mellitus type 2” AND “education” AND “smartphone”. Systematic review ini menggunakan 10 artikel yang sesuai dengan kriteria inklusi. Hasil: Peningkatan penggunaan teknologi dalam pengobatan diabetes memfasilitasi peningkatan komunikasi antara perawat dan pasien. Teknologi jaringan sosial berkembang dengan kecepatan yang mengesankan. Kemajuan terbaru dalam kesehatan keliling (mHealth) telah menciptakan peluang baru untuk meningkatkan manajemen diri DMT2 melalui alat untuk memfasilitasi makan sehat, olahraga, dan akses ke pelayanan kesehatan. Salah satu model inovatif seperti melibatkan sistem terintegrasi yang menghubungkan pasien via ponsel smartphone dengan jaringan dukungan mereka. Kata kunci: diabates mellitus tipe 2; smartphone; edukasi